Enhanced degradation of crystal violet dye using multi-phase doped ZrO2 and HfO2 catalysts - Carriello, Giovanni Miraveti; Pegoraro, Guilherme Manassés; Alves, Lucas Repecka; Assis, Amanda Stefanie Jabur de; Oliveira, Juliana Cristina Ramos de; Santos, Gabriela; Duarte, Iolanda Cristina Silveira; Menezes, Aparecido Junior de; Mambrini, Giovanni Pimenta (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The study investigated the efficiency of zirconium oxide (ZrO2) and hafnium oxide (HfO2) based materials doped with Ag and Pr in the degradation of the dye crystal violet, a mutagenic and carcinogenic compound widely used in industrial processes. Due to their high solubility in water, synthetic dyes represent a challenge for removal by conventional methods, requiring more effective approaches. The research revealed that the presence of multiple phases in the studied materials significantly increases the efficiency in dye degradation, with values ranging between 66% ± 3 and 71% ± 5, suggesting that the diversity of phases provides a greater variety of active catalytic sites. In contrast, single-phase materials, such as ZrO2 and HfO2 stabilized in cubic and monoclinic phases, respectively, showed lower degradation rates, all below 37% ± 11.